ANALISIS PENERAPAN BUDAYA KAIZEN PADA SEKTOR PUBLIK - Febiola Vena Anisa (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to examine how the Kaizen culture is used in the public sector. The author identifies Kaizen concepts that can be adopted and adapted to the context of the public sector through qualitative research conducted in various government agencies. The findings of the analysis show that implementing a Kaizen culture in the public sector has a number of advantages. First of all, implementing the Kaizen concept stimulates staff participation and increases job happiness. The increase in everyone's motivation and performance is the result of this. The application of Kaizen also improves work procedures and reduces waste in the public sector. Improved operational effectiveness can lead to cost savings. The implementation of Kaizen culture in the public sector, however, is not without its difficulties, as this study also found. The complete adoption of Kaizen concepts is hampered by elements such as bureaucratic rigidity, opposition to change, and a lack of resources. This study suggests taking strategic actions to address this issue, such as the formation of a Kaizen team made up of committed workers, suitable training, and unwavering backing from top management. Additionally, collaboration between public and commercial institutions can be a way to share expertise in putting the Kaizen culture into practise. This paper's conclusion is that the public sector has a great opportunity to increase service effectiveness and quality by embracing a Kaizen culture.